Open Innovation’s Barriers In Creating Idea’s Explosion: A Conceptual Framework - Hendrati Dwi Mulyaningsih; Ani Wahyu Rachmawati; Aminuddin Irfani; Nurdin Nurdin (Research Synergy Foundation, 2021)
Open innovation has been developing in the digital revolution era. Many research and references refer to how open innovation can influence the work process, productivity and other factors. The research focusing on how to generate the model of open innovation barriers to create idea’s explosion in innovation process. In detail, the research intent to investigate open innovation barriers from two factors comprise of Inside-in Factors and Inside-out factors. The research applied desk research method to provided conceptual and meta-analysis focusing on integration and proposing new relationships open innovation barriers comprise inside-in factor and inside-out factor. The conceptual and meta-analysis result provide two important factors of open innovation barriers consist of inside-in factor and inside-out factor. Inside-in factor refers barriers which come up by internal factors in the organization or firms itself. On the other hand, inside-out factor refers to barriers which come from external organization or firm. The managerial implication of the research can be applied in organization or firm which use open innovation process in their workflow or model business. Previous research has already identified three levels of analysis of barriers in open innovation, first level is internal level of firms, second level is innovation system of policies and third level is innovations funding and cultural level. Hence, the novelty of the research intent to investigate open innovation barriers from two factors comprise of Inside-in Factors and Inside-out factors